2013
DOI: 10.1016/j.immuni.2013.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Fc Receptor Expression in Dendritic Cells Mediates Protective Immunity against Colorectal Cancer

Abstract: SUMMARY Cancers arising in mucosal tissues account for a disproportionately large fraction of malignancies. IgG and the neonatal Fc receptor for IgG (FcRn) have an important function in the mucosal immune system which we have now shown extends to the induction of CD8+ T cell-mediated anti-tumor immunity. We demonstrate that FcRn within dendritic cells (DC) was critical for homeostatic activation of mucosal CD8+ T cells which drove protection against the development of colorectal cancers and lung metastases. Fc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
141
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(149 citation statements)
references
References 54 publications
5
141
0
3
Order By: Relevance
“…Although the FcRn C-terminal (intracellular) domain contains motifs that may be associated with endocytosis and trafficking, 57,58 it lacks the immunoreceptor tyrosine-based activation motif (ITAM) and immunoreceptor tyrosine-based inhibition motif (ITIM) that are associated with the transmembrane signalling observed with other Fc receptors. 59 Although Baker et al 60 reported that in dendritic cells, interaction between FcRn and immune complexes can lead to secretion of IL-12, to our knowledge there is no mention in the literature of cellular signalling that occurs as a result of FcRn binding its natural ligands, IgG or albumin. The induction of cytokine release by stimulation of FcRn-expressing cells directly was therefore considered to be low.…”
Section: Resultsmentioning
confidence: 99%
“…Although the FcRn C-terminal (intracellular) domain contains motifs that may be associated with endocytosis and trafficking, 57,58 it lacks the immunoreceptor tyrosine-based activation motif (ITAM) and immunoreceptor tyrosine-based inhibition motif (ITIM) that are associated with the transmembrane signalling observed with other Fc receptors. 59 Although Baker et al 60 reported that in dendritic cells, interaction between FcRn and immune complexes can lead to secretion of IL-12, to our knowledge there is no mention in the literature of cellular signalling that occurs as a result of FcRn binding its natural ligands, IgG or albumin. The induction of cytokine release by stimulation of FcRn-expressing cells directly was therefore considered to be low.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, antibody effector functions that are mediated by Fcγ receptors are also compromised during persistent infections, an effect attributed to formation of antigen/ antibody immune complexes (ICs), suggesting that high concentrations of preexisting ICs can limit the effectiveness of antibody therapy in human cancer (137). Moreover, certain immunoglobulins exhibit an antitumorigenic function (138). B lymphocytes are also present in the tumor microenvironment and in mouse models of squamous cell carcinoma, where they promote progression by activating mast cells and other myeloid cells (139).…”
Section: Foxp3mentioning
confidence: 99%
“…9,10 By contrast, marginating DCs of the tumor microenvironment can cross-present tumor antigens and stably engage tumor-specific T cells. 12 Moreover, DCs in tumor-associated tertiary lymphoid structures signal a Th1 cytotoxic immune contexture and promote a protective immune response mediated by T cells against cancer. 13 Therefore, DCs represent a special population of cells that display different phenotypes and activities at the tumor site as well as exhibit differential pro-tumorigenic and anti-tumorigenic functions.…”
mentioning
confidence: 99%